Numerical Investigation of the Effect of Equivalent Ratio on Detonation Characteristics and Performance of CH4/O2 Rotating Detonation Rocket Engine - Xiao Xu; Qixiang Han; Yining Zhang (Aerospace)
Equivalent ratio (ER) is an important factor affecting detonation characteristics and propulsion performance of rotating detonation rocket engine (RDRE). In this paper, the effects of different equivalent ratios detonation characteristics and thrust performance of methane-oxygen RDRE were studied by 2D numerical simulation. The premixed reactants were injected through the injection holes to simulate the discrete injection of reactants on the injection panel in actual RDRE, the number of injection holes was 60 and 120. The results show that there is hybrid detonation mode (HDM), co-direction multi-wave detonation mode (CMM) and unstable detonation mode (UDM) in detonation combustion due to the influence of equivalent ratio and the number of injection holes, and the co-directional multi-wave detonation mode is beneficial to the thrust stability of RDRE. At the last, the number of detonation waves in RDRE decreases with the increase in the equivalent ratio, and the specific impulse (Isp) increases with the increase of the equivalent ratio.